What's mine is yours: The crossover of day-specific self-esteem - Niessen, Cornelia; Unger, Dana; Sonnentag, Sabine; Neff, Angela (Journal of Vocational Behavior, 2012)
This diary study examines the daily crossover of self-esteem within working couples. By integrating self-esteem research into the crossover framework, we hypothesized that the day-specific self-esteem experienced by one partner after work crosses over to the other partner. Furthermore, we proposed that this daily crossover process is moderated by the other partner's general level of self-esteem and empathic concern. We conducted a diary study over five consecutive working days among 102 working couples. Multilevel analyses using the actor-partner interdependence model supported our hypotheses. Day-specific self-esteem experienced by one partner after work crossed over to the other partner in the evening, particularly when this partner had a generally low level of self-esteem and a generally high level of empathic concern. © 2012 Elsevier Inc.